ON the Openness of Functors of k-Nonexpanding and Weakly Additive Functionals - Karchevs’ka, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We study the property of openness of the functors for k -nonexpanding and weakly additive functionals. In particular, it is shown that these functors preserve the openness of mappings between finite compact sets but they are not open.